Answer:
B. (-2,-4)
Explanation
Given equations:
y = 3x + 2
y = -2x - 8
Solving both equations will yield the values of x and y;
Solution:
y = 3x + 2 ----- (i)
y = -2x - 8 ------ (ii)
Using substitution method, input equation i, into ii
3x + 2 = -2x - 8
Collect like terms and solve;
3x + 2x = -8 -2
5x = -10
x = -2
Then put x = -2 into i, to find y
y = (-2 x 3) + 2
y = -6 + 2 = -4
So, the solution of the equation is B. (-2,-4)
ns +sb = 5.4 cm
sb = en so en can be plugged in for sb
therefor es = 5.4
What is the third term of the sequence defined by the recursive rule f(1)=3 f(n)=f(n-1)+4
Need f(2):
f(2)=f(2-1)+4
f(2)=f(1)+4
f(2)=(3)+4=7
FIND f(3):
f(3)=f(3-1)+4
f(3)=f(2)+4
f(3)=(7)+4
f(3)=11
Answer:
A) $0.11
Step-by-step explanation:
Since a dozen (12) eggs cost $1.35. You will divide $1.35 by 12. And it will equal 0.1125. Round it up it equals to 0.11.